2013
DOI: 10.1093/hmg/ddt055
|View full text |Cite
|
Sign up to set email alerts
|

Astroglial FMRP-dependent translational down-regulation of mGluR5 underlies glutamate transporter GLT1 dysregulation in the fragile X mouse

Abstract: Fragile X syndrome (FXS) is a neurodevelopmental disorder caused by the loss-of-function of fragile X mental retardation protein (FMRP). The loss of FMRP function in neurons abolishes its suppression on mGluR1/5-dependent dendritic protein translation, enhancing mGluR1/5-dependent synaptic plasticity and other disease phenotypes in FXS. In this study, we describe a new activation function of FMRP in regulating protein expression in astroglial cells. We found that astroglial glutamate transporter subtype glutam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 54 publications
5
72
1
Order By: Relevance
“…Altered Glu transport has been recently reported in Fmr1 KO astrocytes co-cultured with either WT or Fmr1 KO neurons (53). However, unlike our present finding in the preCGG KI model, Fmr1 KO astrocyte cultures showed similar levels of expression of both GLT-1 and GLAST when compared with WT controls.…”
Section: Discussioncontrasting
confidence: 73%
“…Altered Glu transport has been recently reported in Fmr1 KO astrocytes co-cultured with either WT or Fmr1 KO neurons (53). However, unlike our present finding in the preCGG KI model, Fmr1 KO astrocyte cultures showed similar levels of expression of both GLT-1 and GLAST when compared with WT controls.…”
Section: Discussioncontrasting
confidence: 73%
“…Genetic and pharmacological manipulations of transporter expression (Rothstein et al, 2005;Omrani et al, 2009;Goodrich et al, 2013;Higashimori et function. For example, genetic ablation of the neuronal glutamate transporter EAAC1, which constitutes a small fraction of the total glutamate clearance capacity, alters glutamatergic signaling and synaptic plasticity (Scimemi et al, 2009;Holmseth et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, it was recently reported that Glu uptake is reduced in cortical extracts of the FMR1 KO mice, although this is thought to be mediated by GLT1; Downregulation of mGluR5 and GLAST were also observed in these fractions at early but not at later developmental stages (Higashimori et al 2013). The preCGG KI mice show rotarod deficits (Van Dam et al 2005), and subtle but significant increased foot slips on the ladder rung test that could be analogous to a mild ataxia (Hunsaker et al 2011), and poor skilled forelimb motor learning (Diep et al 2012).…”
Section: Discussionmentioning
confidence: 99%